Analisis Profiling Surat Wasiat Bunuh Diri Ibu Paruh Baya: Studi Kasus Linguistik Forensik - Diliana, Ekfindar; Klau, Ricardo Goncalves (Lembaga Yasin AlSys, 2023)
This study intends to (1) identify the features of language in a middle-aged mother named Pini's suicide will in Talang Village, Sendang District, Tulung Agung on October 23, 2022, and (2) identify the motive for suicide in this case. This study is a qualitative descriptive study that analyzes language aspects using Osslon's (2008) forensic linguistics theory. The investigation yielded (1) the language elements in Pani's suicide will, written by a 41-year-old woman in Tulungagung, were a text structure with certain characteristics that are common in suicide notes, as stated by prokofyeva (2013), there were many spelling, punctuation, and letter errors capital, the use of the pronoun 'aku', and grammar which used a lot of declarative sentences (commands), and some of the emotions implied by the words in the will show emotions of doubt, despair, and the actors' desperation stems from a lack of self-control in the face of unforeseen occurrences. In this scenario, it's conceivable that she was stressed out because her ex-husband remarried. (2) While the perpetrator's suicide was considered to be motivated by mental problems such as depression. This could be seen in various word choices that demonstrated the players' desperation as a result of their inability to control themselves in unforeseen situations. In this scenario, it's conceivable that she was stressed out because her ex-husband remarried. Furthermore, the offender feels alone and without family support; this is classified as egoistic suicide due to a lack of social engagement with people closest to them.